2015
DOI: 10.1111/hepr.12569
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects and chemoprevention of dimethylaminoazobenzene‐induced hepatocarcinogenesis: A review

Abstract: The lipophilic azo dye dimethylaminoazobenzene (DAB) is a potent hepatocarcinogen accounted as a group-2B carcinogen causing risk to humans. DAB is commonly used as a coloring agent in food, pharmaceuticals, beverages, soap and polishes. The exploration of DAB-induced hepatocarcinogenesis in animal models helped to an extent to perceive the histological, biochemical and molecular mechanisms of DAB carcinogenesis and also the severity of DAB exposure to humans. In experimental animal models, it is well-proved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In the same line, our histopathological data revealed that the liver tissue of mice that received DAB/PB has many pathological changes that indicate the HCC such as hepatocyte degeneration, loss of hepatic architecture, multiple lymphoid stroma aggregations, and congestion of hepatic blood vessels, and this indicates that exposure to DAB/PB can cause significant and extensive damage to the liver tissue, leading to the formation of HCC. This is further supported by the findings of Thomas et al ( 2016 ), who identified additional changes in the liver, such as hyperplasia of the hepatic parenchyma cells, loss of contact inhibition, and damage of the central vein of the liver lobules.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the same line, our histopathological data revealed that the liver tissue of mice that received DAB/PB has many pathological changes that indicate the HCC such as hepatocyte degeneration, loss of hepatic architecture, multiple lymphoid stroma aggregations, and congestion of hepatic blood vessels, and this indicates that exposure to DAB/PB can cause significant and extensive damage to the liver tissue, leading to the formation of HCC. This is further supported by the findings of Thomas et al ( 2016 ), who identified additional changes in the liver, such as hyperplasia of the hepatic parenchyma cells, loss of contact inhibition, and damage of the central vein of the liver lobules.…”
Section: Discussionsupporting
confidence: 76%
“…HCC development was confirmed by histopathology analysis that showed atypical lesions of HCC; this may be due to the catabolism of DAB by cytochrome P-450 enzymes, which results in the creation of reactive oxygen species (ROS), toxic electrophiles, and DNA adducts that produce liver tumors (Thomas et al 2016 ). Oxidative stress is a crucial factor in the growth of cancers (Kensler and Trush 1984 ), due to reactive oxygen and nitrogen species (ROS and RNS) that can interact with DNA bases to form promutagenic DNA adducts (Bartsch and Nair 2006 ).…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that metabolizing DAB by cytochrome P450 enzyme releases many electrophiles and reactive oxygen species (ROS). The ROS can interact with DNA, leading to conformational alterations that can potentially contribute to tumorigenesis [ 4 ]. According to a recent research conducted by Lu et al [ 5 ], it was shown that reducing the proportion of ROS and electrophiles generated may lead to a substantial reduction in the occurrence of DNA structural alterations, often referred to as adducts.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with ISH, the CtSDR-based imaging strategy involves fewer operation steps and has a shorter turnaround time. Moreover, it is worth noting that the DAB used in ISH is carcinogenic and has the potential to induce skin and bladder cancer ( 49 ). In contrast, the proposed imaging strategy is DAB-free and more environmentally friendly.…”
Section: Resultsmentioning
confidence: 99%